Poly(ethyleneimines) in dermal applications: biocompatibility and antimicrobial effects. - Wiegand, Cornelia; Bauer, Marius; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2013)
Cationic polyamines, such as poly(ethyleneimines) (PEIs), may recommend themselves for antimicrobial applications as they can interact with microbial membranes resulting in their disruption. The purpose of the study was the assessment of biocompatibility and antibacterial activity of PEIs with different architectures (branched (b) and linear (l)) and molar masses (0.8-750 kDa). lPEI and bPEI exhibited a strong antibacterial activity against Staphylococcus aureus and Escherichia coli with a more pronounced effect on the Gram-positive bacteria. lPEIs further demonstrated a higher antibacterial efficacy compared to bPEIs but no significant differences between 5 and 25 kDa were observed. In accordance, antibacterial activity of bPEI did not specifically depend on molar mass. Only slightly lower minimal inhibitory concentrations (MIC) were observed at 5 kDa (S. aureus) and 25 kDa (E. coli) in the tests. As PEIs are compelling candidates for use in antimicrobial treatment, two basic aspects have to be investigated: treatment effectiveness and safety. PEIs clearly induced molecular weight dependent cytotoxic effects in vitro. PEIs with low molecular weight (0.8 and 5 kDa) exhibited higher biocompatibility. Nonetheless, the results confirmed a low genotoxic potential of lPEI and bPEIs. In conclusion, 2.5 kDa-lPEI and 0.8 kDa-bPEI can be recommended for use as antimicrobial polymers in dermal applications due to their high biocompatibility with concomitant antibacterial efficacy. Copyright © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13